Palm Oil Mill Solid Waste Generation and Uses in Rural Area in Benin Republic: Retrospection and Future Outlook - Koura, Tatiana W.; Dagbenonbakin, Gustave D.; Kindomihou, Valentin M.; SINSIN, Brice A. (My University, 2017)
Palm oil is one of the major oil crops in the world, producing important vegetable oils in the world oil and fats market. Its production generates solid wastes whose sustainable management is crucial for the oil chain development in oil palm producing countries. Benin Republic is a small oil palm producing country where oil palm plays social, cultural, and economic roles for farmers. This chapter analyzes the linkage between improvement of palm oil process extraction and palm oil mill solid waste (POMSW) management for sustainable palm oil production. Composed mainly of fibers, the two kinds of POMSW are empty fruit bunches (EFBs) and press mesocarp fibers (PMFs), which are rich in units’ fertilizers and are renewable energy. POMSW in Benin Republic is used in agriculture, in cosmetic, or as energy. The upgrade of traditional mills generates POMSW use as a boiler fuel to reducing wood necessity and increasing farm profit. As this use is not sustainable, research must be made to generate electricity with POMSW and its use for crop fertiliza‐ tion, to ensure environment protection, enhance contribution to food security, restore degraded soils, and increase earnings of producers of rural areas.
Keywords: POMSW; improvement of palm oil process extraction; electricity; fertilization; rural area